Profil efek samping kaptopril pada pasien hipertensi di Puskesmas Denpasar Timur I periode Oktober 2017 - Diatmika, I Kadek Dwi Putra; Artini, Gusti Ayu; Ernawati, Desak Ketut (E-Jurnal Medika Udayana; Vol 7 No 5 (2018): E-Jurnal Medika Udayana, 2018)
Captopril is one of the most commonly prescribed antihypertensive drugs because it is affordable and effective for lowering blood pressure, but captopril also has some side effects. This research was conducted to find out the side effect profile of captopril in Puskesmas Denpasar Timur I. The research method used was descriptive observational with cross sectional design and sample were selected by using consecutive sampling method. Samples were 100 respondents who met the criteria of inclusion and exclusion. The results of the study found that 87% of respondents experienced side effects of captopril, while 13% of respondents did not experience any side effects. Based on the 87%, aged> 60 years (44%) and aged 20-60 years (43%). The majority of side effect occurred in women (63%), while men (24%). The most common side effects of captopril use were dry cough (76%), dizziness (50%), dry mouth (30%), constipation (12%), itchy spots (8%), taste disorder (6%), and redness in the skin (4%). Most respondents experienced more than one type of side-effect from the use of captopril. Keywords : Side effects, hypertension, captopril